2019
DOI: 10.1021/acs.biochem.9b00045
|View full text |Cite
|
Sign up to set email alerts
|

The Thioredoxin System Reduces Protein Persulfide Intermediates Formed during the Synthesis of Thio-Cofactors in Bacillus subtilis

Abstract: The biosynthesis of Fe−S clusters and other thio-cofactors requires the participation of redox agents. A shared feature in these pathways is the formation of transient protein persulfides, which are susceptible to reduction by artificial reducing agents commonly used in reactions in vitro. These agents modulate the reactivity and catalytic efficiency of biosynthetic reactions and, in some cases, skew the enzymes' kinetic behavior, bypassing sulfur acceptors known to be critical for the functionality of these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 91 publications
2
12
0
Order By: Relevance
“…The disulfide reduction rate is an important factor for cellular function. In B. subtilis , evidence suggests that the redox flux of the Trx system modulates the rate of sulfide production in cysteine desulfurase and the activity of the Trx system also depends on the rate of disulfide formation [ 45 ]. Furthermore, evidence from crystal structure analysis indicates that only one out of two binding sites of the B. cereus TrxR homodimer is occupied with NADPH, indicating a possible asymmetric co-substrate binding in TrxR [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The disulfide reduction rate is an important factor for cellular function. In B. subtilis , evidence suggests that the redox flux of the Trx system modulates the rate of sulfide production in cysteine desulfurase and the activity of the Trx system also depends on the rate of disulfide formation [ 45 ]. Furthermore, evidence from crystal structure analysis indicates that only one out of two binding sites of the B. cereus TrxR homodimer is occupied with NADPH, indicating a possible asymmetric co-substrate binding in TrxR [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus trxA trxB Thioredoxin and thioredoxin reductase genes respond to oxygen and disulfide stress Uziel et al, 2004 Helicobacter pylori trxA and trxC trxR Required for colonization and survival Baker et al, 2001 Mycobacterium tuberculosis trxA, trxB and trxC trxR Needed for survival against reactive oxygen and nitrogen species produced by activated macrophages Trivedi et al, 2012 Bacillus subtilis TrxA trxA and trxB Needed for survival and virulence Zheng et al, 2019 Escherichia coli trxA and trxC trxB Used to prevent oxidative damage from reactive nitrogen intermediates St. John et al, 2001;Potamitou et al, 2002 Thioredoxin reductase is part of the pyridine nucleotidedisulfide oxidoreductase family.…”
Section: Bacteria Trx Genes Trxr Genes Function Referencesmentioning
confidence: 99%
“…However, excess sulfide is toxic to cells [ 6 ]. It inhibits cellular respiration by poisoning cytochrome c oxidase or raises oxidative stress with reactive sulfur species [ 7 , 8 ]. We have recently reported that most heterotrophic bacteria are actively producing H 2 S during growth, and many of them can oxidize self-produced H 2 S by using sulfide: quinone oxidoreductases (SQR) [ 9 ] or flavocytochrome c-sulfide dehydrogenases (FCSDs) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In bacteria, the sqr and pdo genes are often next to each other to form operons on the chromosome ( 9 ). Further, rhodanese (RHOD, EC 2.8.1.1) genes are often clustered with sqr and pdo genes with some being even fused with SQR or PDO [ 8 , 11 , 14 ]. RHODs are also ubiquitous in all three domains of life [ 17 ].…”
Section: Introductionmentioning
confidence: 99%